2008
DOI: 10.1007/s00192-008-0612-0
|View full text |Cite
|
Sign up to set email alerts
|

Midurethral sling outcomes: tension-free vaginal tape versus Pelvilace

Abstract: We sought to compare the complications and efficacy of tension-free vaginal tape (TVT) and Pelvilace. Chart reviews and telephone questionnaires documented complications, urinary symptoms [Urogenital Distress Inventory short form (UDI-6) and Patient Global Impression of Improvement (PGII)], and re-operations. Failure was defined as PGII > or = 4 (no change or worse) or reoperation for urinary incontinence. There were 91 TVT and 22 Pelvilace slings. The TVT group had lower rates of urinary retention beyond 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Voiding difficulty is another common complication after TVT. We reported voiding difficulty to occur in 11.6%; this is considerably less than reports by Shippey et al 11 who reported 40% short-term voiding difficulty. However, Freeman et al 12 reported that only 5.8% required catheterisation, and Schierlitz et al 10 reported that 8.5% had short-term catheterisation.…”
Section: Discussioncontrasting
confidence: 65%
“…Voiding difficulty is another common complication after TVT. We reported voiding difficulty to occur in 11.6%; this is considerably less than reports by Shippey et al 11 who reported 40% short-term voiding difficulty. However, Freeman et al 12 reported that only 5.8% required catheterisation, and Schierlitz et al 10 reported that 8.5% had short-term catheterisation.…”
Section: Discussioncontrasting
confidence: 65%
“…Synthetic (mesh) midurethral slings are the most studied surgical treatment and the current 'gold standard' for SUI [3,86]. Although non-synthetics have reported similar success [47,[87][88][89][90][91], mesh has lower complication rates including decreased urethrolysis, urinary retention and reoperation [89][90][91][92][93][94]. In POP repair, polypropylene has demonstrated greater anatomical success during sacral colpopexy than autologous or biological materials [95][96][97].…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Shippey et al performed a retrospective cohort study with prospective follow-up of patients with polypropylene and porcine dermal slings. 17 The synthetic group had lower rates of urinary retention (8 percent versus 43 percent; p Ͻ 0.001) and reoperation for retention (1 percent versus 19 percent; p Ͻ 0.001). Failures based on subjective incontinence symptoms or reoperation for stress incontinence occurred in 24 percent of porcine dermal slings versus 10 percent of synthetic slings (p ϭ 0.10).…”
Section: Treatment Of Stress Incontinence Slingsmentioning
confidence: 95%
“…In contrast, Bai et al found that autologous rectus fascia slings had a higher cure rate (93 percent) compared with retropubic colposuspensions (88 percent) and synthetic slings (87 percent) 23 (Table 2). [15][16][17][18][19][20][21][22][23][24][25] A recent meta-analysis concluded that traditional slings using a variety of materials (porcine dermis, dura mata, fascia lata, vaginal wall, autologous dermis, and rectus fascia) appear to be as effective as minimally invasive slings, but have higher rates of adverse events. 26 Patients with porcine dermal slings may be at an increased risk of urinary retention and reoperation because of variation in the host response to the biological material compared with the predictable response to polypropylene mesh.…”
Section: Plastic and Reconstructive Surgery • November Supplement 2012mentioning
confidence: 98%